الفكر العمراني عند أبن الشعّار الموصلي من خلال كتابه(قلائد الجمان في فرائد شعراء هذا الزمان) (University of Mosul-college of Basic Education, 2011)
صنف ابن العشار الموصلي (ت 654هـ/1256م) كتابه (قلائد الجمان في فرائد شعراء هذا الزمان)، وقد سلط فيه الضوء على الجوانب العمرانية والحضارية من خلال الشخصيات التي ترجم لها، فتحدث عن العمران الثقافي والعلمي من خلال ترجمته للعلماء ومنجزاتهم، وعن العمران الاقتصادي من خلال ترجمته للتجار وأصحاب المهن، وعمران المنشآت المعمارية من خلال ذكره للخطط في المدن التي مرت بكتابه، وكذلك تناول العمران السياسي من خلال حديثه عن الخلفاء والوزراء والأمراء الذين ترجم لهم، كما تناول العمران الديني من خلال حديثه عن المذاهب الفقهية لمن ترجم لهم.Ibn Al-Sha'aar Al-Mosuli (died 654 A.H.) wrote a book known as "Qalaa'id Al-Juman fi Faraa'id Shu'araa' hatha Az-Zaman" which means "exquisite poems in this period". In this book, he shed light on architectural and cultural aspects throughout the biographies for whom he wrote. He talked about the cultural and scientific progress through the biography of the scientists. Similarly, he talked about the economic progress through what he wrote about trader and profession men. Architectural progress also has its portion in his book. Likewise, he mentioned the political developments as he talked about caliphs, ministers, and princes mentioning their biographies. Finally, he tackled the religious aspects mentioning the juristic schools and their scholars for whom he wrote biographies.